Importance économique du Port Autonome de Liège: rapport 2002 - Frédéric Lagneaux (National Bank of Belgium, 2004)
– This paper provides an extensive overview of the economic importance and development of the Port Autonome de Liège, over the period 1997 - 2002. Focusing on the three major variables of value added, salaried employment and investment, it also provides information about the financial situation of some vital segments in this inland port. In addition, it includes figures with respect to the ongoing growth of several cargo traffic segments and attempts to establish a link between these and the progress of the production in the industries at stake. The breakthrough of this research - compared to its first edition issued last year - consists of evaluating the indirect effects of the sectors in question in terms of value added and employment. A few refinements have also been made, such as the routine geographical and functional selection of companies according to the cluster they belong to (NACE-Bel code approach), the limitation of administrative work incurred, the review of the company-size analysis, etc. Annual reports data from the Central Balance Sheet have been computed for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. For the estimation of indirect effects, Supply and Use Tables from the National Accounts Institute have been resorted to. The developments in inland ports are numerous nowadays, as a parallel to the ever congesting road networks and the growing maritime traffic (e.g. increase in containerized shipments). The Port Autonome de Liège is the second largest inland port in Europe and therefore plays an important role in the development of inland waterways and of their traffic. Moreover, as it is the case for the maritime ports, the increase in scale and specialization of the vessels inevitably impacts the operation of this port. Production, trade and transport are no longer considered as individual, isolated activities, but are integrated within a single system. Therefore, ports have to evolve from mere centres of transport (discharging and loading of vessels) to logistic centres. The Port Autonome de Liège is a very good example of this evolution as it offers high-quality connections with the railways, motorways and the Liège airport. Intermodality is a great asset for the Port Autonome de Liège and is the spearhead of its future.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments.; Hafenentwicklung; Hinterland; Lüttich